Polysaccharide Thin Solid Films for Analgesic Drug Delivery and Growth of Human Skin Cells - Maver, Tina; Mohan, Tamilselvan; Gradišnik, Lidija; Finšgar, Matjaž; Stana Kleinschek, Karin; Maver, Uroš (Frontiers in Chemistry, 2019)
Chronic wounds not only lower the patient`s quality of life significantly, but also present a huge financial burden for the healthcare systems around the world. Treatment of larger wounds often requires the use of more complex materials, which can ensure a successful renewal or replacement of damaged or destroyed tissues. Despite a range of advanced wound dressings that can facilitate wound healing, there are still no clinically used dressings for effective local pain management. Herein, alginate (ALG) and carboxymethyl cellulose (CMC), two of the most commonly used materials in the field of chronic wound care, and combination of ALG-CMC were used to create a model wound dressing system in the form of multi-layered thin solid films using the spin-assisted layer-by-layer (LBL) coating technique. The latter multi-layer system was used to incorporate and study the release kinetics of analgesic drugs such as diclofenac and lidocaine at physiological conditions. The wettability, morphology, physicochemical and surface properties of the coated films were evaluated using different surface sensitive analytical tools. The influence of in situ incorporated drug molecules on the surface properties (e.g. roughness) and on the proliferation of human skin cells (keratinocytes and skin fibroblasts) was further evaluated. The results obtained from this preliminary study should be considered as the basis for the development ‘real’ wound dressing materials and for 3D bio-printing applications.